Optimization of the electrical energy consumption in the classrooms of the faculty of economic and business sciences of the Universidad Ricardo Palma - Huarcaya Calle, Diana (2018)
The objective of the research is to propose an alternative to optimize the electrical consumption in the classrooms of the Faculty of Economic and Business Sciences (FACEE) of the Ricardo Palma University. It was identified that the classrooms had a high consumption of electrical energy, lighting is done with fluorescent tubes, users do not turn off the lights when they finish their activities. LED panels and motion sensors are the best alternative for their characteristics, the implementation of this alternative is more efficient and would contribute to optimize the electric power and as a consequence the cost.